MAPPING FUNCTIONS OF A PROCESS BASED ON A FUNCTIONAL RESONANCE ANALYSIS: ACTION RESEARCH USED IN A PIG PRODUCER UNIT - Steinke, Alexandre; Rosário, Cláudio Roberto; Flach, Douglas (Revista Gestão da Produção Operações e Sistemas, 2020)
Purpose – This study aims to map the process functions of the Piglet Breeding Unit. Theoretical framework - The study highlights a literary review of resilience engineering, the holistic view, process modeling and the socio-technical system. Design/methodology/approach – Based on the Functional Resonance Analysis Method (FRAM) and using Action Research as a research methodology to guide study steps. Findings - Practical applications of the study have provided a projection of room for maneuver in operations, allowed operations to be viewed in a macro scope, supporting the decision made by managers and instigated them to rethink the way each function was performed. The actions proposed through the study meet the process management, seeking to identify and reducing production bottlenecks, from the perspective of production engineering. Originality/value – Mapping the process using aspects related to each function provides a reflection of actions that would allow the unit manager to cooperate in defining the best decision based on the structure and the level of importance in the system used. FRAM allows the level and type of variability to be increased, allowing the function with the largest number of variables to be seen. Keywords - Decision making, management processes, function mapping, production bottlenecks.